EFFECTS OF FISH PARASITES ON THE RELATIVE CONDITION FACTOR (Kn) OF THE FISHES IN THE RESERVOIRS OF PERAK RIVER, MALAYSIA - Ibrahim, Ado Abdulmalik; Yahaya, Zary Shariman; Hashim, Zarul Hazrin (FUDMA Journal of Sciences, 2025)
This research presents the effects of fish parasites infection on the relative condition factor (Kn) of fishes sampled from Chenderoh, Bersia and Temengor Reservoirs of Perak River. Fishes were examined for Parasites in the reservoirs, The fishes were infected with parasites belonging to 8 taxonomic groups, Protozoa, Myxozoa, Monogenean, Digenean, Cestoda, Nematoda, Acanthocephala and Crustacean. The mean Kn values of the fishes showed that 78 infected and 38 uninfected fishes have a good condition factor, 30 infected and 35 uninfected fishes have poor condition factor. This showed that the effects of parasites in infected fish Kn depends on the virulence of the parasites and availability of food to the fish hosts.